Opinion of medical students compared with non-medical students about organ donation and its bioethical conflicts - Muñoz-Niklitschek, Esteban; Morales-Delgado, Paulo; Muñoz-Oyarzo, Emilio; Parra-Venegas, Rogelio (Journal of Education, Health and Sport, 2021)
Introduction and Purpose: Organ donation is controversial. Chilean legislation failed to increase donors. However, it seems that there is an enthusiasm to be an organ donor, so education is important. Therefore, medical students play an important role in educating, but the other students may not know these topics. Thus, the following work pretends to compare the opinions of medical students and non-medical students at the University of Concepción (UDEC) about organ donation and associated bioethical conflicts. Material and Method: Observational, descriptive, cross-sectional study with qualitative and quantitative variables. It was used a 16-question survey, applied in Argentina, adapted to the Chilean culture. The sample was 60 students: 30 medical students and 30 students from other fields, outside the health area. Microsoft Windows Excel program was used to process the data. Results: Mostly men were surveyed, on average 21.5 years. Engineering was more frequent after medicine, and mode was 4 years studied. The absence of belief predominated. In both groups the donation was considered good; that they would donate, because it is a way of giving a life; and what they would like to receive. In medicine they considered that those who donate are brave people, where the other group considered that they give their lives and are brave. Regarding the concepts of brain death and Chilean law number 20.413, knowledge was lower in the non-medical group. Conclusions: We observe that medical university students handle some concepts related to donation in more detail than those who pursue careers outside the health area. Organ donation it is an issue that needs to be brought to discussion that should include the government authorities, local authorities, and the community.